Revisiting the definition and concept of Filipino family a psychological perspective - Tarroja, Maria Caridad H. (Philippine journal of psychology, 2010)
"This paper reviews the current definition of Filipino families, starting from a sociological perspective to the challenge to Filipino psychologists."